Cryoballoon vs. laser balloon ablation for atrial fibrillation: a meta-analysis - Sun, Xiaochi; Zhao, Shenyu; Yu, Simin; Cui, Kaijun (Frontiers in Cardiovascular Medicine, 2023)
Background Cryoballoon ablation (CBA) and laser balloon ablation (LBA) are two innovative ways for the treatment of atrial fibrillation (AF). This study aimed to evaluate the efficacy and safety of cryoballoon ablation and laser balloon ablation in patients with AF. Methods We searched Pubmed, Embase, Ovid, Web of Science and other databases for comparative trials comparing CB and LB ablation in the treatment of AF, from establishment of database to August, 2023. Results A total of 13 studies and 3,582 patients were included (CBA, n = 2,308; LBA, n = 1,274). There was no difference between CBA and LBA in acute PVI rate per vein, 12-months recurrence rate of AF, 12-months recurrence rate of atrial arrhythmia, occurrence rate of pericardial tamponade, occurrence rate of inguinal complications. LBA presented a lower acute PVI rate per patients (CBA 97.0% vs. LBA 93.4%, RR = 1.04, 95%CI: 1.01–1.07). Transient nerve palsy was more likely to occur after CBA (CBA 2.7% vs. LBA 0.7%, RR = 4.25, 95%CI: 2.06–8.76). However, the occurrence of persistent nerve palsy between CBA and LBA groups were similar (CB 1.4% vs. LB 1.0%, RR = 1.09, 95%CI: 0.55–2.14). In terms of procedural duration, the procedural time of CBA was shorter than that of LBA (WMD = −26.58, 95%CI: −36.71–16.46). Conclusions Compared with LBA, CBA had a shorter procedural duration. There was a higher incidence of transient but not persistent phrenic nerve palsy after CBA. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=272607 Identifier (CRD42021272607).